Analysis of the Relationship between IoT Integration and Digital Skills Training on Competency Development and Employee Performance at Bogor Start-up - Nurohman, Dwi Aris; Setiawati, Rahmi; Vandika, Arnes Yuli (West Science Interdisciplinary Studies, 2024)
This study investigates the relationship between IoT integration and digital skills training on competency development and employee performance in start-up companies in Bogor. Utilizing a quantitative approach, data were collected from 170 respondents through a structured questionnaire employing a Likert scale ranging from 1 to 5. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) to explore the interconnections between the variables. The findings indicate that all examined relationships are positive and significant. Specifically, IoT integration and digital skills training significantly enhance competency development, which in turn positively impacts employee performance. These results underscore the importance of technological integration and continuous skills training in fostering employee growth and organizational performance within the dynamic environment of Bogor start-ups. The study provides valuable insights for managers and policymakers aiming to leverage digital advancements to optimize human capital and achieve superior business outcomes.